Efficiency of Using PowerPoint Presentations in the Teaching of General Chemistry - Urbanová, Klára (Scientia in educatione, 2020)
In the years 2006–2010 the research has been conducted on the use of PowerPoint presentations in the general chemistry teaching. Primarily it focused on the search for the form of presentation that will bring needed clarity to the teaching and will increase the effectiveness of teaching. It also focused on the elimination of possible negative effects of the presentations on the educational process. This article summarizes the theoretical background of the work, a brief description of research methodology and discussion of results and conclusions. It presents in detail the part of research focused on finding and assessing freely downloadable presentations for teaching chemistry.